Rancang Bangun Aplikasi Coffee Shop Berbasis Visual Basic - Ferdiansyah, Erik; Amri, Fakhrudin Rifki; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
The development of the coffee shop industry requires technological support to enhance efficiency in daily operations. Coffee shops often face challenges in managing transactions and sales reports, which are still performed manually, leading to potential errors and time inefficiencies. This research aims to design a Visual Basic-based application as an effective solution for recording transactions, monitoring orders, managing menus, and generating sales reports. The application development follows the waterfall methodology, which includes requirements analysis, system design, implementation, and documentation. The results of this research indicate that the developed application effectively improves the operational efficiency of coffee shops by speeding up transaction processes, reducing recording errors, and providing accurate sales reports. Additionally, the interface is designed to be simple and user-friendly, allowing employees to use the application without requiring technical expertise. By implementing this application, coffee shops can manage their business effectively, support strategic decision-making, and enhance service quality for customers.